Population Dynamics in a Noisy World: Lessons From a Mite Experimental System - Benton, Tim G.; Beckerman, Andrew P. (Advances in Ecological Research, 2005)
This chapter presents an overview of ongoing studies of a soil mite laboratory system. It describes the impact of noise on population dynamics. It shows that there is no simple mapping of the environment onto dynamics (alternatively, populations subject to the same environmental sequence do not respond in the same way). The chapter uses time series analysis to try to reconstruct important aspects of the biology driving the dynamics and asks the question ‘‘if we know the environmental stochasticity, how much does it improve our ability to detect the underlying biology?’’ The chapter discusses experiments at the life-history level that provide insight into the way that the organisms respond to the environment. In particular, it has been shown that there is considerable plasticity in the life history of the organisms and the way they respond to density, which means that the observed life history is the result of a complex interplay between current conditions, past conditions within the organisms' lifetimes, and the conditions experienced by previous generations. Understanding the plasticity in the life history allows considerable insight into the way that population dynamics may be shaped by environmental heterogeneity.